Evaluation of Pregnant Women, Fetuses and Infants with Zika Virus Exposure and Infection: Lessons Learned from the Congenital Zika Program at Children's National. (4th October 2017) - DeBiasi, Roberta; Mulkey, Sarah; Cristante, Caitlin; Pesecreta, Lindsay; Vezina, Gilbert; Bulas, Dorothy; duPlessis, Adre
Abstract: Background: ZikaVirus (ZIKV) infection during pregnancy has severe potential consequence to the fetus. Despite limited endemic transmission in the continental US, travel/ sexual exposurein the periconception/pregnancy period requires experienced multidisciplinary care to assess potential infection and effects in the fetus. Methods: The Congenital Zika Program at Children's National (CZPCN) was developed to meet need for pre- and post-natal consultation in the setting of Zika exposure/infection during pregnancy. CZPCR includes multidisciplinary expertise in fetal imaging, pediatric infectious diseases, fetal and pediatric neurology. Services include a hotline, facilitation of ZIKV testing and interpretation, detailed fetal MRI/US, delivery instructions to faciliate postnatal evaluation of ZIKV exposed/infected fetuses and educational outreach to providers regarding ZIKV. Results: Between Jan 2016 and May 2017, 36 women/fetuses were evaulated atby CZPCN for possible ZIKV infection during pregnancy (32 US residents who traveled, 2 with partner who traveled, 2 emigrees). An additional 14 women/infant pairs were evaluated following postnatal referral to our program. Exposure route included direct arboviral (89 %) and/or potential sexual exposure (48%). Symptoms occurred in only 6/50 (12%). Exposure occurred in the preconceptual period in 10/50 (20%), first trimester in 23/50 (46%), second trimester in 13/50 (26%), and third trimester 4/50 (8%). Nearly 50% (24/50) of women presented outside the 12 week window of exposure and could not have infection excluded. ZIKV was confirmed in 22% (11/50) or suspected due to unspecified flavivirus infection in 28% (14/50). Only 7/50 (14%) had negative PCR/IgM testing in appropriate window to exclude infection. Two fetuses with severe involement were not carried to term, 1 was carried to term but died immediately after birth and 1 died within the first year of life. Conclusion: CZPCN fills a critical need within our region to faciliate evaluation of exposed/infected pregnant women/fetuses/infants including neurodevelopmental followup of affected suriving infants. . Lessons learned are instructive to other centers developing programs, needed as the range of endemic Zika transmission expands. Disclosures: All authors: No reported disclosures.